2018
DOI: 10.1021/acsami.8b07999
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Investigation of Evaporated Perovskite Absorbers with High Crystal Quality on Different Substrates

Abstract: Dual-source vapor-phase deposition enables low-temperature fabrication of high-performance planar structure perovskite (CHNHPbI) solar cells (PSCs), applicable in tandem devices or for industrial production with high homogeneity. Herein, we report low-temperature fabrication of high-efficiency PSCs by dual-source vapor-phase deposition and significance of TiO surface modification with [6,6]-phenyl C butyric acid methyl ester (PCBM) on cell performance. Co-evaporation of PbI and CHNHI, as confirmed by X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 30 publications
(63 reference statements)
1
54
1
Order By: Relevance
“…The cells, for example, fabricated with perovskite compounds using a mixture cations of methylamine, formamidine, cesium, and rubidium have provided high photovoltaic conversion efficiencies of beyond 20 % owing to their wide light absorption and high‐quality perovskite layer formation . Their facile fabrication processes, light weight and possible flexible structures, and low material costs have also led to discussions on replacing conventional solar cells with these still developing perovskite cells and utilizing them in a tandem configuration . However, the low durability of the perovskite cells derived from the decomposition of perovskite compounds upon exposure to ambient air remains a problematic issue .…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The cells, for example, fabricated with perovskite compounds using a mixture cations of methylamine, formamidine, cesium, and rubidium have provided high photovoltaic conversion efficiencies of beyond 20 % owing to their wide light absorption and high‐quality perovskite layer formation . Their facile fabrication processes, light weight and possible flexible structures, and low material costs have also led to discussions on replacing conventional solar cells with these still developing perovskite cells and utilizing them in a tandem configuration . However, the low durability of the perovskite cells derived from the decomposition of perovskite compounds upon exposure to ambient air remains a problematic issue .…”
Section: Introductionmentioning
confidence: 74%
“…[14][15][16] Their facile fabrication processes, light weight and possible flexible structures, and low material costs have also led to discussions on replacing conventionals olar cells with these still developing perovskite cells and utilizing them in a tandem configuration. [17][18][19][20] However,t he low durability of the perovskite cells derived from the decomposition of perovskite compounds upon exposure to ambient air remains ap roblematic issue. [21,22] Haquea nd co-workersf ound that the degradation of the organo-lead halide perovskite layer in the presence oxygen is an important factor influencing stability.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite solar cell fabrication processes can be classified into five methods (Supplementary Tables 1 and 2). One of the strong candidates is the evaporation incorporated process [27][28][29] . With a hybrid process combining evaporated precursor and solution-based conversion processes, Sahli et al reported a 25.2% perovskite/fully textured silicon tandem solar cell 30,31 .…”
mentioning
confidence: 99%
“…There are various methods such as evaporation, vacuum deposition, atomic layer deposition, sputtering, etc. to fabricate a conformal perovskite film and other components of the PSC on a textured substrate 47 52 . In this regard, one can use a two-step hybrid technique combining co-evaporation and spin-coating to deposit perovskite on an underlying textured silicon wafer 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Since, on the one hand, the proposed structure has to be fabricated from the bottom up, and each layer should follow the shape of the previous layer, and on the other hand, the presented nanostructured PSC has angled configuration with a low width unit cell, after the fabrication process, it would not accurately form as proposed and would have a shape similar to the one shown in Fig. 7 a, depending on the manufacturing conditions 47 , 49 , 50 , 53 .…”
Section: Resultsmentioning
confidence: 99%